"Chłop polski w Europie i Ameryce" a problem relacji pomiędzy badaniami socjologicznymi a ich aplikacjami dla potrzeb rozwiązywania problemów społecznych - Cichocki, Ryszard; Jankowska, Klaudia (Człowiek i Społeczeństwo, 2019)
The article attempts a reconstruction and an in-depth characterization of the connections between basic sociological research and their applications for solving social problems. For W.I. Thomas and F. Znaniecki, social phenomena and processes that arose in American cities under the influence of mass migration processes at the turn of the 19th century constituted the starting point of their research program. By conducting sociological research, originally intended as applied sociological research, they decided that in order to create conditions for rational social control over socially unacceptable phenomena it was crucial to formulate a theoretical model, which would serve as a basis for describing, explaining and predicting the researched phenomena. Consequently, it would allow presenting the key conditions for creating rational techniques for controlling the environment on the basis of scientific research. The present article contains an analysis of the following elements: assumptions regarding the rational technique models, the relationship between the aforementioned type of technique and other techniques, the relationship between this type of technique and theoretical knowledge in social sciences, assumptions with respect to scientific knowledge in sociology that it needs to meet in order to constitute a foundation for solving social problems strategies. Ryszard Cichocki, Klaudia Jankowska, „Chłop polski w Europie i Ameryce” a problem relacji pomiędzy badaniami socjologicznymi a ich aplikacjami dla potrzeb rozwiązywania problemów społecznych [„The Polish Peasant in Europe and America” and the problem of relations between sociological research and its applications for solving social problems] edited by M. Nowak, „Człowiek i Społeczeństwo” vol. XLVII: „Chłop polski w Europie i Ameryce” po stu latach [Polish peasant in Europe and America after one hundred years], Poznań 2019, pp. 19–35, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.